O распределении момента первого выхода из интервала и величины перескока границы для процессов с независимыми приращениями и случайных блужданий - Каданков, В.Ф.; Каданкова, Т.В. (Український математичний журнал, 2005)
Для однорідного процесу з незалежними проростами отримано інтегральні перетворення сумісного розподілу моменту першого виходу процесу з інтервалу і величини перестрибу процесу через границю в момент виходу, сумісного розподілу supremum, infimum і значення процесу. For a homogeneous process with independent increments, we determine the integral transforms of the joint distribution of the first-exit time from an interval and the value of a jump of a process over the boundary at exit time and the joint distribution of the supremum, infimum, and value of the process.